A Growing Concern: Long Commutes and Mental Fatigue Among Workers - Mohd Suadi Nata, Dayana Hazwani; Mohamad Jamil, Putri Anis Syahira; Muhammad Rawee, Mira Nursabrina (Makara Journal of Health Research, 2024)
Background: Commuting stress is a growing concern for workers with long daily journeys between home and work. This study explores the effects of commuting on workers’ mental and physical health, focusing on stress, mental fatigue, and productivity at work. Methods: The research conducted in Selangor, Malaysia, involved 212 commuters who completed a survey that included sociodemographic and commuting information, the Depression Anxiety and Stress Score (DASS-21), and a mental fatigue questionnaire. Results: The findings revealed that a significant proportion of workers experienced stress from their commuting routines: approximately 74.5% reported that commuting had a detrimental effect on their mental health, while 82.1% experienced mental fatigue, which directly impacted their ability to concentrate and perform effectively at work. The DASS-21 results showed that 14.2% experienced mild depression, 16% had moderate anxiety, and 11.4% reported mild stress. A significant positive correlation was found between commuting distance and anxiety (r = 0.35, p < 0.05), stress (r = 0.32, p < 0.01), and mental fatigue (r = 0.42, p < 0.05). Conclusions: Commuting stress adversely affects concentration, productivity, and well-being. The study suggests adopting telework, flexible work hours, and workplace mental health initiatives to mitigate these negative effects.